Perancangan Sistem Informasi Penjualan Dan Jasa Perbaikan Mobil Pada Bengkel Alam Jaya - Intan Permata; Fachruddin; Hendri (Jurnal PROCESSOR, 2020)
Alam Jaya Workshop is an individual company engaged in services or repairs of four-wheeled vehicles located on 32 Tidore Street. In processing the data, both sales data, customer data, goods data, purchase data and reports on Alam Jaya Workshop are still not well computerized. The data processing system used in Alam Jaya Workshop is currently still manual, where the service data search process is slow and difficult because the data is not well coordinated, making reports slow if the report is needed immediately, the accuracy of the data is not guaranteed. All these problems arise because of the lack of good organization in processing data and in making reports, it is still recorded in the agenda book, resulting in slow performance. Therefore, this study aims to provide a solution to the problems that occur by offering sales information and maintenance service along with purchasing system using Unified Modeling Language (UML) to design the system modeling such as Use Case Diagram, Activity Diagram and Class Diagram as well PHP programming language, MySQL DBMS with Adobe DreamweaverCS5 editor and waterfall system development method. There are several stages in doing this research that is problem identification, literature study, data collection, data analysis, system design and report writing. The result of this study is a system that can provide effectiveness and efficiency in processing data at Alam Jaya Workshop.